Effects of Perfusion, Coronary Artery Disease Burden, and Revascularization in Establishing Organized Cardiac Rhythm During Extracorporeal Cardiopulmonary Resuscitation for Shockable Refractory Out‐of‐Hospital Cardiac Arrest - Ruben Crespo‐Diaz; Marinos Kosmopoulos; Ganesh Raveendran; Sergey Gurevich; Demetris Yannopoulos; Jason A. Bartos (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The aspects of extracorporeal cardiopulmonary resuscitation critical for reestablishing an organized rhythm and subsequent functional survival are unclear. This study characterizes the impact of reperfusion with extracorporeal membrane oxygenation (ECMO) and percutaneous coronary interventions (PCI) on achieving an organized rhythm in patients with refractory shockable out‐of‐hospital cardiac arrest (OHCA). Methods and Results Two hundred eighty‐nine consecutive patients in refractory shockable OHCA were placed on ECMO followed by coronary angiogram (n=289) and PCI (n=165). Patients were grouped based on the extracorporeal cardiopulmonary resuscitation stage where a sustained organized rhythm was achieved. Survival outcomes were evaluated by using the Cerebral Performance Category. Logistic regression analysis was performed to determine the relationship between Cerebral Performance Category and timing of organized rhythm. Standard advanced cardiac life support before hospital arrival resulted in 148 of 289 (51%) patients attaining an organized rhythm while 87 of 289 (30%) achieved an organized rhythm post ECMO cannulation but before PCI, and 37 of 289 (13%) achieved an organized rhythm following PCI. Obstructive coronary artery disease was observed in 192 of 289 (66%) patients. A total of 144 of 192 (75%) patients with obstructive coronary artery disease converted to an organized rhythm before PCI and 37 of 192 (19%) following PCI. Cerebral Performance Category score 1 or 2 was significantly more likely in patients with cardiac arrest and obstructive coronary artery disease who achieved an organized rhythm before PCI (odds ratio [OR], 3.9 [95% CI, 1.2–12.0], P=0.024). Conclusions Most patients undergoing extracorporeal cardiopulmonary resuscitation for refractory OHCA due to shockable rhythms achieved an organized rhythm before PCI independent of coronary artery disease burden. Also, neurologically favorable survival was more prevalent in those attaining an organized rhythm before PCI.